Individualized Treatment for Advanced Non-Small Cell Lung Cancer: A Case Report and Literature Review - Sun, Qianqian; Li, Weiqing; Liu, Taorui; Guo, Huiqin (Frontiers in Oncology, 2022)
The incidence of lung cancer is high and about 75% of the patients with lung cancer were found in the middle and advanced stage, which has limited treatment strategy. Non-small cell lung cancer (NSCLC) accounts for about 85% of all lung cancers. In this article, we delineate the treatment process of a middle-aged male patient with advanced stage lung cancer to explain the significance of individualized chemotherapy combined with immunotherapy and surgery. This patient has extensive bone metastasis and a PS scores of 2. After nine cycles of preoperative neoadjuvant chemotherapy, surgery, and two cycles of postoperative adjuvant chemotherapy, the patient achieved complete response (CR) and his PS score was 0. Although there is a standard chemotherapy regimen for lung adenocarcinoma, the treatment effect varied because of individual difference. Comprehensive analysis of the characteristics of patients through a variety of means to develop a precise individualized chemotherapy plan will be a major direction of lung cancer treatment in the future. Additionally, surgical treatment for patients with advanced lung cancer after chemotherapy can effectively reduce the primary lesion and prolong the survival time of patients.